De l’(in-)hospitalité des lieux urbains pour les enfants - Nadja Monnet (Strenae)
Faced with a diagnosis that has been known for several decades, and is increasingly hammered home by the media, of a desertion of outdoor spaces by certain young people in many of our Western cities, this text looks at the causes of this situation and points to new trends underway, based on existing literature but also on field experience. The author points the ways in which space is made available for children, as well as the ways in which children take their place in the spaces they frequent everyday.